A Fun Autodidactic Learning Model for Students to Improve Second Language Understanding - Heru Pratikno; Zainul Muttaqin (IJLECR (International Journal of Language Education and Cultural Review), 2024)
Learning a second language, for example, English is often considered difficult by most students. In fact, this foreign language is very important for them in further studies and the world of work. Therefore, this research aims to determine a fun autodidactic learning model for students to improve second language understanding Apart from that, the writer also wants to know what methods students are interested in and effectively use in honing their English skills independently. Research data was obtained by filling out a questionnaire in the form of questions to determine the effectiveness of the interest learning model. The research respondents were Unisba Statistics students. After the data was collected, this research used quantitative descriptive methods to analyze it. This identification is carried out to reveal learning methods, problems encountered in learning, and efforts made in improving students' English skills. The results obtained based on this research are an effective independent method or model of learning English that is of interest to students, including through songs as a medium for teaching new languages and improving vocabulary and grammar. Apart from that, a fun autodidactic learning model, namely through communicative films and games, can also improve their English pronunciation skills. However, the popular method still has several obstacles, namely students do not know the pronunciation and structure of English according to grammatical rules.